Analisis Modal Kerja dan Pengelolaan Keuangan pada UMKM (Studi Kasus pada UMKM Afza Frozen Food Di Kota Metro) - Kinanti, Sekar; Suyanto, Suyanto; Sari, Gustin Padwa (Expensive: Jurnal Akuntansi dan Keuangan, 2023)
This research aims at working capital and financial management in SMEs Afza Frozen Food in Metro City. This type of research is descriptive research with a qualitative approach. The data analysis technique used is using a qualitative descriptive analysis tool that is describing the data that has been obtained from the data collection technique used. The results of the study show that the working capital contained in UMKM Afza Frozen Food always experiences fluctuations that are not so significant. The provision and use of efficient working capital affects the level of profit or profit, this occurs in Afza Frozen Food SMEs, where the higher the working capital used, the higher the operating profit generated. Afza Frozen Food does not manage its finances well, this can be seen from the absence of planning, recording, reporting and financial management processes, resulting in unclear profit/loss result.